Robust control of a single-phase VSI with LCL filter for grid-tie and islanded operation modes applied to PV distributed generation in microgrids environment - Pena, Jose C. U. [UNESP]; Melo, Guilherme [UNESP]; Canesin, Carlos A. [UNESP]; Sampaio, Leonardo P.; IEEE (Ieee, 2014)
This paper introduces a methodology to model and control a single-phase inverter with LCL filter intended for low power PV distributed generation in microgrid scenario. The system should operate in grid connected and island modes with a smooth transition between them. The control strategy is to split the system into two: the internal voltage subsystem and the external injected current subsystem. These two subsystems are modeled in state-space considering disturbances and uncertain parameters. By using linear matrix inequalities (LMI) two state-feedback H-infinity controllers are designed. The complete simulation results demonstrate the feasibility of the proposed control system.